Combating IUU Fishing in Indonesia’s EEZ: A State Responsibility Perspective - Septaria, Ema; Iskandar, Iskandar; Md. Khalid, Rasyikah (Faculty of Law, Universitas Jambi, 2026)
Background: Illegal fishing remains one of the most significant threats to the sustainability of marine resources and maritime governance in many coastal states, including Indonesia. The problem becomes particularly complex in maritime areas where Indonesia’s Exclusive Economic Zone (EEZ) borders the jurisdiction of neighbouring states. From the perspective of international law, coastal states possess sovereign rights as well as legal responsibilities to manage and conserve fishery resources within their EEZ in accordance with the United Nations Convention on the Law of the Sea (UNCLOS) 1982. However, persistent illegal fishing activities conducted by foreign fishing vessels indicate that the implementation of these legal responsibilities remains challenging. Objectives: This article examines Indonesia’s responsibility under international law in managing fishery resources in EEZ areas bordering other states and addressing illegal fishing practices. Methodology: The research employs normative legal research using statutory, comparative, and philosophical approaches to analyse relevant international legal principles, including state sovereignty, sovereign rights over natural resources, and sustainable development in fisheries governance. Findings: The study finds that although Indonesia has adopted several regulatory and enforcement measures to combat illegal fishing, significant legal and institutional challenges remain, particularly regarding transboundary fisheries management and regional cooperation. Originality/Novelty: Strengthening Indonesia’s responsibility under international law, combined with enhanced regional cooperation and sustainable fisheries governance, is essential for ensuring effective management of fishery resources and combating illegal fishing in bordering EEZ areas.